Tracing the Level of TPCK among Secondary EFL Teachers in Bangladesh (Teacher’s World: Journal of Education and Research, 2024)
The overall English language proficiency level of school learners in Bangladesh presents a gloomy picture despite the initiatives taken in the last two decades to reform English language education. The deteriorating capacity of English as a foreign language (EFL) teacher is often considered a significant barrier to English language education outcomes in Bangladesh. Technological Pedagogical Content Knowledge (TPCK), a framework comprising various knowledge required for enhancing teachers’ quality, is a less explored phenomenon among secondary EFL teachers in Bangladesh. The purpose of the quantitative study was to trace the level of TPCK among secondary school EFL teachers in Bangladesh. This paper was conducted through a questionnaire survey of 120 secondary EFL teachers located in metropolitan and suburban areas of Dhaka, the capital city. It revealed from the study that content knowledge was evident among the highest number of EFL teachers, while pedagogical knowledge was found among the lowest number of teachers. The study also reported a significant influence of teachers’ age, gender, experiences, and locations on their various knowledge types.Teacher’s World: Journal of Education and Research, 49 (1), 95-115